(3QSGdI aj GdCSe hGdeSeis - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ef YdjfG HGdgOi hCfge hUdi Gddg Ydi eMeO hYdi Bdg hSde , SCdJfi CYRc Gddg HGdJbhi YeG cKQ ajg NhV GdNGFVjf ef CeQ GdGSe hGdeSei hbdJ cja jUM Cf CMOgeG gh GdBNQ s
(3BNQgG (B:s
(3GdHGH GdQGHY ai JHjjf cja jchf GdTF GdhGMO eSei ef Lgg hJSejI ef LgI CNQi agPG eG MVQfi CYRc Gddg ef Gdbhd ai GdGSe hGdeSei ced GdcdGe ai GdGSe hGdeSei s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HBNQg eWGdYI HGSe YHO GdQMef Ydi Hf CMeOs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1107/4) s
Keywords: (3Gdabg GdESdGejs